Diffuse infiltrative hepatocellular carcinoma or cirrhosis? - Koza, Jarosław; Świątkowski, Maciej (Journal of Education, Health and Sport, 2017)
The case of a patient whose imaging tests indicated liver cirrhosis is presented. The detailed diagnostic reveals advanced hepatocellular carcinoma (HCC). Alpha-fetoprotein and a blind liver biopsy was necessary. The authors conclude that in oncological surveillance of patients with cirrhosis, not only ultrasound but also AFP should be included.